A unified framework for the organization of the primate auditory cortex - Baumann, Simon; Petkov, Christopher I.; Griffiths, Timothy D. (Frontiers in Systems Neuroscience, 2013)
In nonhuman primates a scheme for the organisation of the auditory cortex is frequently used to localise auditory processes. The scheme allows a common basis for comparison of functional organisation across nonhuman primate species. However, although a body of functional and structural data in nonhuman primates supports an accepted scheme of nearly a dozen neighbouring functional areas, can this scheme be directly applied to humans? Attempts to expand the scheme of auditory cortical fields in humans have been severely hampered by a recent controversy about the organisation of tonotopic maps in humans, centred on two different models with radically different organisation. We point out observations that reconcile the previous models and suggest a distinct model in which the human cortical organisation is much more like that of other primates. This unified framework allows a more robust and detailed comparison of auditory cortex organisation across primate species including humans.